Pemetaan Potensi Pencemaran Di Daerah Tangkapan Mata Air Tuk Tlogorejo Kabupaten Magelang - Nitis Aruming Firdaus; Awaluddin Setya Aji; Rafli Gifari Prayoga (Universitas Prof. Dr. Hazairin, S.H, 2022)
Citrosono Village is a village located on the slopes of Mount Merbabu, Mount Andong and Telomoyo, precisely in Grabag sub-district, Magelang regency, Central Java province and because it is on the slopes of a mountain, the air can be felt quite cool in this village. Citrosono Village has a population of 5060 people according to the 2010 national population census, while the area of Citrosono Village is 567.87 ha, and the catchment area of the spring with the largest discharge is the Tuk Tlogorejo spring, the Tuk Tlogorejo spring is also used as clean water. by the local community and as a source of raw water by PDAM Magelang Regency. Identify potential pollution in tuk tlogorejo spring catchment area. Analyzing the quality of springs based on Permenkes 416 in 1990 on the standard requirements of clean water quality. To map the potential pollution point of Magelang Regency for the determination of the range category or so-called claiming in three range categories. Analysis of the point map of potential pollution and distance from the spring to pollution is done by scoring. Scoring is performed by combining weighting results from distance and potential pollution. Based on the results of the analysis obtained 3 classes of pollution potential levels in Citrasono Catchment Area, namely low, medium, and high classes. The result of classification of broncaptering condition level is good, moderate and bad condition. With the result of potential pollution as many as 11 low levels, 111 moderate levels, and 73 high levels from citrasono catchment area.